Methodologies for the Determination of Blood Alpha1 Antitrypsin Levels: A Systematic Review - Borja Ruiz-Duque (MDPI AG, 2021)
Background: The study of hematic concentrations of alpha1 antitrypsin (AAT) is currently one step in the diagnosis of AAT deficiency. To try to clarify the relevance of the laboratory techniques, we carried out a systematic review of the literature. Methods: Studies evaluating the quantification of AAT in peripheral blood were searched in PubMed in July 2021. The selection criteria included (1) any type of study design that included a quantification of AAT in peripheral blood; (2) studies written in English or Spanish; (3) studies evaluating human beings; and (4) studies involving adults. Results: Out of 207 studies, the most frequently used techniques were nephelometry (43.9%), followed by ELISA (19.8%) and turbidimetry (13.5%). Altogether, 182 (87.9%) cases expressed their results in units of gram, while 16 (7.7%) articles expressed them in units of mole. Only 2.9% articles referred to the standard used, 43.5% articles indicated the commercial kit used, and 36.2% indicated the analyzer used. Conclusions: The technical aspects of these determinations are not always reported in the literature. Journals should be attentive to these technical requirements and ensure that they are included in the works in which AAT is determined in order to ensure a correct interpretation of the study findings.